2020
DOI: 10.3389/fpsyg.2020.00858
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Concept of an Eclectic, Integrative Therapeutic Approach to Mental Health and Well-Being Through Virtual Reality Technology

Abstract: This research involving human participants was reviewed and approved by the health sciences research ethics board of Western University, Canada. All participants provided informed consent prior to participation. The authors have no potential conflicts of interest to disclose. The authors also note that no adverse events occurred throughout the conduct of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 78 publications
(79 reference statements)
1
26
0
Order By: Relevance
“…Previous research has revealed the promise of VR for inducing positive affect in response to guided meditation practices when conducted within pleasant computer graphical environments viewed through HMD (Frewen et al, 2020;Miller et al, 2021;Mistry et al, 2020;Navarro-Haro et al, 2017 and has also demonstrated the application of immersive 360°videos of similarly pleasant but real-world recorded environments for use in meditation practice also viewed through HMD (Bennett, 2018;Tarrant et al, 2018). However, as much as these prior demonstrations have facilitated immersive meditative experiences in various virtual settings, these previous meditations involved decidedly solitary activities; meditative instructors were not visually depicted within the scenes (c.f., Cikajlo et al, 2016, who used avatars).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has revealed the promise of VR for inducing positive affect in response to guided meditation practices when conducted within pleasant computer graphical environments viewed through HMD (Frewen et al, 2020;Miller et al, 2021;Mistry et al, 2020;Navarro-Haro et al, 2017 and has also demonstrated the application of immersive 360°videos of similarly pleasant but real-world recorded environments for use in meditation practice also viewed through HMD (Bennett, 2018;Tarrant et al, 2018). However, as much as these prior demonstrations have facilitated immersive meditative experiences in various virtual settings, these previous meditations involved decidedly solitary activities; meditative instructors were not visually depicted within the scenes (c.f., Cikajlo et al, 2016, who used avatars).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrating the efficacy of conducting meditation practices within these graphical virtual environments, especially for improving positive affect and wellbeing (e.g., relaxation; Frewen et al, 2020;Mistry et al, 2020;Navarro-Haro et al, 2017. For example, Mistry et al (2020) showed that, as compared to closely matched non-VR meditations, VR meditation was associated with heightened experiences of certain positive emotions, most notably awe, particularly when the VR meditation preceded rather than followed practice of the non-VR meditation in a repeated measures design.…”
mentioning
confidence: 99%
“…Further, it was our impression that the order effect we observed in the present study was at least partially attributable to method variance, whereby participants randomized to complete non-VR meditation first rated this experience in a way that was perhaps overly favorable due to the fact that they had not yet experienced VR meditation, producing a relative ceiling effect for comparisons with VR meditation. A more comparative assessment such as conducted in the study by Frewen et al (2020) may therefore be less sensitive to a possible order effect if indeed this can be viewed as a nuisance variable or artifact rather than a bona fide result of theoretical or clinical significance. On the other hand, our research design comparing the effect of eyes-open versus eyes-closed conditions during non-VR only as a between-groups factor limits investigation of this effect, and future researchers might rather employ three meditations in a fully balanced within-subjects design.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we were cognizant of the fact that meditation practices are often conducted with participants' eyes closed, and so we also required to include this condition for external validity purposes. Frewen et al (2020) provide justification of the use of both experimental control conditions in comparisons of response between VR and non-VR tasks.…”
Section: Materials and Proceduresmentioning
confidence: 98%
See 1 more Smart Citation